Scholarly Productivity at the University Of Ghana, 1960-1970: Implications for University Library Development - Fosu, V.K. (Ghana Library Journal, 2000)
This work looks at schola rly productivity at the University of Ghana from ] 900 to 1970. The s tudy hds brought out an issue of low productivity during the period. Low funds, the poor publishing industry in Ghana, lack of equipment with which to do research, among others have been noted as problems affec ting scholarly publishing at the University of Ghana. Some suggestions have been made for the improvement of scholarly output at the University of Ghana.